Of beast and beauty eaudiobook - Hahn, Chanda (Daughters of Eville, 2019)
Seven vengeful sisters. Seven fairytale kingdoms. Seven daughters of Eville. Everyone dreams of marrying a prince—except for me. I am nothing more than a pawn in my adoptive mother's diabolical plot against the seven kingdoms. I was the chosen tool, her sharpened blade that would cut the deepest into the heart of the kingdom of Baist. But like all deadly weapons, my wedding is two-edged sword that could cost me my soul. For I am Rosalie, one of the adopted daughters of Lady Eville, and it is my duty to enter into a loveless and hate-filled marriage with the narcissistic Crown Prince of Baist. My choices and heart are not my own to give. Yet even in the thick of dire situations, beastly vengeance can give way to beautiful attraction.